Teak (Tectona grandis) Plantation: Factors Influencing to Teak Plantation Area Changes of Smallholders during the Year of 2010-2020 in Luang Prabang, Lao PDR. (Case study in Kok Ngiew, Sen Khalok and Thin Some villages) - DONSAVANH, Beun; MANYVONG, Anoukone; PHETDONEMO, Phaivanh; SENGMANY, Foling; PHONCHALUEN, Sengkham; VONGPACHANH, Chantai; NOPO, Mongxiong; BOUAPHAKEO , Pazeun; SOUKANYA, Kongkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The study on factors influencing teak plantation area changes during 2010 to 2020 in Luang Prabang province was to identify the factors that affect shifting of smallholder’s teak growth to other land uses. This research employed the mixed research method for research design with the specific sample for teak plantation holding from 2010 to 2020 in three communities such as Kok Ngiew, Sen Khalok, and Thin Some villages with the total of 88 teak growers, and village landowner individually for 44, 33, and 11, respectively. The research applied the Enter Method of Multi-Linear Regression Model for identifying the factors influencing teak stand area changes, and showed the study results in descriptive and coefficient statistical analysis. Consequently, the result of this study found that the teak stand area decreased more than 50 percent (69.82 percent or 69 hectares) from 2010 to 2020 in 10 years. These areas have changed to other land uses such as crop cultivation land, land for construction, and unused land. Hence, this result especially found that there are three significant factors that affect the teak plantation area changes of p-value <0.05 and 0.001, which are the market demand for wooden teak products, seasonal cultivation instead of teak, and household economy. These factors pushed teak owners to stop all teak stand areas including mature and young teak raise more household income. As a result, this study proposes the result to the government for policy-making decision for achieving the Sustainable Development Goal (SDG) as well as the sustainability of forest management onto National Development Plan in the future. Due to wood area declines amount of tree stand, it will be lacks wood consumption from tree plantation then it causes to alter using wood increasingly from natural resource instead.